2022
DOI: 10.1002/jls.21825
|View full text |Cite
|
Sign up to set email alerts
|

Centering Socially Just Leadership: An Integrated Model for Contextualizing Leadership Learning

Abstract: The current article introduces an integrated model centering culturally relevant leadership learning and incorporating the leadership learning framework through social justice pedagogy. The integrated model for contextualizing leadership learning addresses how a leadership educator informs the leadership learning process through their identity, culture, and commitment. By acknowledging these influences, educators can begin to address social justice in developing leadership learning opportunities for students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The integration of the CRLL model (Bertrand Jones et al., 2016) and the leadership learning framework (Guthrie & Jenkins, 2018) produced the integrated model of contextualized leadership learning (Guthrie & Beatty, 2022) is crucial. Fully integrating these models is useful not only in contextualizing leadership learning but operationalizing the models to be more effective.…”
Section: Integrated Model For Contextualizing Leadership Learningmentioning
confidence: 99%
“…The integration of the CRLL model (Bertrand Jones et al., 2016) and the leadership learning framework (Guthrie & Jenkins, 2018) produced the integrated model of contextualized leadership learning (Guthrie & Beatty, 2022) is crucial. Fully integrating these models is useful not only in contextualizing leadership learning but operationalizing the models to be more effective.…”
Section: Integrated Model For Contextualizing Leadership Learningmentioning
confidence: 99%
“…For example, the growth of social issues in media has made leadership education more complicated which emphasizes the importance of peer leader development to focus on power, privilege, and oppression that is part of our everyday world (Teig, 2018). Holistically, it is important to explore leadership development in an environment that is socially just (Guthrie & Rodriguez, 2018); it is vital to understand the barriers that exist within our campus communities. Even when institutions work to create peer leader groups that are representative of the institution, some have found that barriers persist for certain identities of students because of expectations placed on peer leaders.…”
Section: Socially Just Peer Leadersmentioning
confidence: 99%